NOC and NIC linkages to NANDA-I and clinical conditions : supporting critical reasoning and quality care - Johnson, Marion (Maryland Heights, Missouri : Elsevier Mosby, 2012)
This book provides linkages among the three standardized languages recognized by the American Nurses Organization: NANDA-I, Nursing Outcomes Classification (NOC), and Nursing Interventions Classification.
Languages and development of the linkages / Sue Moorhead and Joanne McCloskey Dochterman -- Use of linkages for clinical reasoning and quality improvement / Howard Butcher and Marion Johnson -- Use of NNN in computerized information systems / Meridean Maas, Cindy Scherb, and Barbara Head Introduction to linkages for actual and health promotion diagnoses -- NOC and NIC linked to nursing diagnosis Introduction to linkages for risk for nursing diagnoses -- Introduction to linkages for clinical conditions -- NOC and NIC linked to clinical conditions
Includes index.
Keywords: NURSING CARE METHODS